Answer:
Step-by-step explanation:
Given the functions z=(x+y)[tex]e^y\\[/tex] and x=u²+v² and y=u²−v²
Using the composite derivative formula;
∂z/∂u= ∂z/∂x*∂x/∂u+∂z/∂y*∂y/∂u
∂z/∂u = y[tex]e^y[/tex]*2u + [(x+y)[tex]e^y[/tex]+x[tex]e^y[/tex]]*2u
∂z/∂u =y[tex]e^y[/tex]*2u + 2u[x[tex]e^y[/tex]+y[tex]e^y[/tex]+x[tex]e^y[/tex]]
∂z/∂u = y[tex]e^y[/tex]*2u + 2u[2x[tex]e^y[/tex]+y[tex]e^y[/tex]]
∂z/∂u = 2u[u²−v²][tex]e^{u^2-v^2}[/tex]+ 2u[2(u²+v²)[tex]e^{u^2-v^2}[/tex]+y[tex]e^{u^2-v^2}[/tex]]]
∂z/∂v= ∂z/∂x*∂x/∂v+∂z/∂y*∂y/∂v
∂z/∂v = y[tex]e^y[/tex]*2v + [(x+y)[tex]e^y[/tex]+x[tex]e^y[/tex]]*-2v
∂z/∂v =y[tex]e^y[/tex]*2v -2v[x[tex]e^y[/tex]+y[tex]e^y[/tex]+x[tex]e^y[/tex]]
∂z/∂v = y[tex]e^y[/tex]*2v -2v[2x[tex]e^y[/tex]+y[tex]e^y[/tex]]
∂z/∂v = 2v[u²−v²][tex]e^{u^2-v^2}[/tex]-2v[2(u²+v²)[tex]e^{u^2-v^2}[/tex]+y[tex]e^{u^2-v^2}[/tex]]